The Efectivenessof using the Monopoly Game with Integrating Hots to Improve Students’ Writing at Tenth Grade of SMK ANDALUSIA Wonosobo - wafiyah, Widad; Lestiyanawati, Rochyani (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2025)
One of the English language skills that must be mastered is writing. It serves as a tool to transfer ideas in written form. In cognitive ability, writing activities fall into the level of creation, which is one of the levels of HOTS (Higher Order Thinking Skills). The objective of this research is to determine whether there is an improvement in writing skills and an increase in HOTS among students using Monopoly games. The method used in this research is the quantitative method. This study focuses on a pre-experimental design with two groups for pre-test and post-test. Data are collected through questionnaires, tests, and documentation. The results of the research indicate that using Monopoly games significantly enhances writing skills among students. The subjects in this study consist of 42 students from class X AKL 1 and X PPLG 1, who undergo pre-test, treatment, and post-test. The test results are analyzed using the Paired Sample T-test in SPSS 27. The findings reveal that the average score of the pre-test was 52.7, while the post-test score was 77.4. These figures indicate that the post-test score is higher than the pre-test score, suggesting that the use of Monopoly games has a substantial impact on students' writing skills. It can be concluded that the Monopoly Game media can be used to enhance the writing skills of students in English learning for class X students of SMK Andalusia Wonosobo.